2017
DOI: 10.1111/imr.12602
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cell death in intestinal pathologies

Abstract: Summary The intestinal tract is a site of intense immune cell activity that is poised to mount an effective response against a pathogen and yet maintain tolerance towards commensal bacteria and innocuous dietary antigens. The role of cell death in gut pathologies is particularly important as the intestinal epithelium undergoes self-renewal every four to seven days through a continuous process of cell death and cell division. Cell death is also required for removal of infected, damaged and cancerous cells. Cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 188 publications
(491 reference statements)
0
42
0
Order By: Relevance
“…Further, the pathogenic role of TNF in Mefv V726A/V726A mice is mediated through TNFR1 while TNFR2 signaling is protective against certain pathologies, including arthritis and colitis. TNF/TNFR1 signaling is involved in proinflammatory cytokine production through NF-κB and MAPK activation and in proapoptotic signaling through the RIPK3/CASP8 axis (63). We have previously shown that, unlike TNFR1 signaling, lack of the While the loss of TNF/TNFR signaling provided substantial protection against all disease characteristics, it was particularly effective against neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the pathogenic role of TNF in Mefv V726A/V726A mice is mediated through TNFR1 while TNFR2 signaling is protective against certain pathologies, including arthritis and colitis. TNF/TNFR1 signaling is involved in proinflammatory cytokine production through NF-κB and MAPK activation and in proapoptotic signaling through the RIPK3/CASP8 axis (63). We have previously shown that, unlike TNFR1 signaling, lack of the While the loss of TNF/TNFR signaling provided substantial protection against all disease characteristics, it was particularly effective against neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
“…55 The attachment of TNF-α to its receptor (TNF-α R) triggered a specific downstream cascade, to facilitate the nucleus translocation of the transcription factor NF-κB and other inflammatory factors, such as TNF-α and IL-6. 57 Indeed, ALA interacted with phosphorylation of IkB-α as an NF-κB suppressant within the cytoplasm by means of either mitogen-activated protein kinase (MAPK) or recycling of vitamin E ( Figure 5). NF-κB-mediated gene transcription and/or translation was vital to regulate the intestinal cell death and to maintain the intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It was evident that the intestinal cell death and homeostasis have been significantly implicated in chronic colitis. 57 Indeed, ALA interacted with phosphorylation of IkB-α as an NF-κB suppressant within the cytoplasm by means of either mitogen-activated protein kinase (MAPK) or recycling of vitamin E ( Figure 5). 12 On the contrary, subsequent to trimerization of TNF-α receptor, and recruitment of TNF receptor-associated factor-2 (TRAF-2) and ribosome inactivating protein (RIP) to death domain (DD), both of the TNF receptor type 1-associated DD protein (TRADD), TNF-α R, and IkB kinase (IKKs) were stimulated either directly [58][59][60][61] ( Figure 5) or indirectly via MAPK kinase 1-MAPK kinase 4-IKK (MEKK1-MKK4-IKK) pathway, which was stymied by ALA at each stage ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…It is only when cell death occurs at a massive scale and when it is induced by non‐physiological stimuli such as infectious pathogens, chemical agents, or irradiation that it results in inflammatory or immune reactions that have an impact on whole‐body physiology . The present issue of Immunological Review is dealing with the mechanistic links between Death, Danger and Immunity .…”
mentioning
confidence: 99%
“…2 It is only when cell death occurs at a massive scale and when it is induced by non-physiological stimuli such as infectious pathogens, chemical agents, or irradiation that it results in inflammatory or immune reactions that have an impact on whole-body physiology. 3,4 The present issue of Immunological Review is dealing with the mechanistic links between Death, Danger and Immunity. Thus, major emphasis is laid on the danger signals that emanate from stressed and dying cells as dangerassociated molecular patterns (DAMPs) or cell death-associated molecular patterns (CDAMPs) and that in fine determine whether cell death results in inflammatory and immune responses or not ( Figure 1).…”
mentioning
confidence: 99%